Pengaruh Kompetensi, Disiplin dan Pemberian Tambahan Penghasilan Pegawai terhadap Kinerja Pegawai pada Dinas Kesehatan Kabupaten Banyuasin - Santi, Juhana; Yustini, Tien (ITB AAS Indonesia Surakarta, 2024)
The research used in this research is a quantitative research method. The population in this study were employees of the Banyuasin District Health Service with a total of 136 ASN people. The sampling in this research was a saturated sample, with 136 respondents. Data collection techniques were carried out through questionnaires using a Likert scale. The results of this research show that from the F test results the F value is 147.542 with a significance of 0.000. Because Fcount > Ftable (2.673) and sig < 0.05, it can be concluded that simultaneously there is a significant influence of Competency, Discipline and TPP on the performance of Banyuasin District Health Service employees. From the results of the t test, it is known that competence, discipline, and TPP each partially have a positive effect on the performance of Banyuasin District Health Service employees. The Coefficient of Determination (R2) is 76.5%. Performance is influenced by Competency, Discipline and TPP, while the remaining 23.5% is the influence of other factors not studied, including motivation, E-performance system and career development. keywords: Competence, Discipline, Additional Employee Income, Employee Performance